A planar thermoelectric power generator for integration in wearable microsystems - Carmo, João Paulo Pereira (2010)
A technique for IC-compatible fabrication of a planar (in-plane) thermoelectric (TE) power generator using a thermopile composed of n-type bismuth telluride (Bi2Te3) and p-type antimony telluride (Sb2Te3) thin-films is presented. The research demonstrates that the thermal co-evaporation of bismuth/antimony (Bi/Sb) and telluride (Te) is the most suitable deposition technique. The measurements showed TE performance properties of the deposited thin-films that are comparable to those reported for the same materials in the bulk form. The measurements showed absolute values of the Seebeck coefficient in the range 91–248 VK−1, an electrical resistivity in the 7.6–39.1 m range and a thermal conduction between 1.3 and 1.8Wm−1 K−1. The best resulting figures-of-merit, ZT, at room temperatures were 0.97 and 0.56 (equivalent to power-factors, PF, of 4.87×10−3 and 2.8×10−3WK−1m−2) for the Bi2Te3 and Sb2Te3 thin-films, respectively. The IC-compatibility and the dependence of the TE performance on technological details, such as photolithography and wet etching used for patterning the thin-films have also been investigated. The converter dimensions for best performance were analysed and a prototype of a planar TE power generator was fabricated.